Application of an activity‐based receptor bioassay to investigate the in vitro activity of selected indole‐ and indazole‐3‐carboxamide‐based synthetic cannabinoids at CB1 and CB2 receptors. Issue 3 (18th November 2018) - Noble, Carolina; Cannaert, Annelies; Linnet, Kristian; Stove, Christophe P.
Abstract: Synthetic cannabinoids (SCs) are the most chemically diverse group of new psychoactive substances. This group has been associated with several intoxications, many with fatal outcomes. Although advancements have been achieved in pharmacology, metabolism, and detection of these compounds in recent years, these aspects are still unresolved for many SCs. The aim of this study was to investigate the in vitro potency of 14 indole‐ and indazole‐based SCs by applying a stable CB1 or CB2 receptor activation assay and correlating the activity with their structure. The half‐maximal effective concentration (EC50 ) of 5‐chloropentyl, 5‐bromopentyl, and 5‐iodopentyl JWH‐122 analogs varied from 74.1 to 283.7 nM for CB1 and 7.05 to 23.4 nM for CB2, where the addition of a chlorine atom enhanced the potency at CB1 compared with the bromo and iodo analogs. AM‐2201 was the most active at CB1 within this naphthoylindole family, with an EC50 of 23.5 nM but with the lowest efficacy (Emax 98.8%). Within the indole‐3‐carboxamide derivatives, 5F‐MDMB‐PICA was the most active compound, with a CB1/CB2 EC50 of 3.26/0.87 nM and an Emax around three times higher than JWH‐018. ADB‐FUBINACA was the most potent tested SC overall, with a CB1/CB2 EC50 of 0.69/0.59 nM, and an Emax around 3‐fold higher than that for JWH‐018 at CB1. The data obtained in this study confirm how small differences in the structure of SCs might lead to large differences in their activity, especially at CB1, which may be correlated with differences in their toxic effects in humans. Abstract : The structure‐activity relationship of synthetic cannabinoids (SCs) was evaluated via their potency (EC50) and efficacy (Emax). Among the halogenated analogs of JWH‐122 (Cl, Br and I in the 5‐pentyl position) the presence of the Cl or Br enhances their efficacy. The L‐tert‐leucinamide and methyl L‐tert‐leucinate derivatives (ADB‐FUBINACA or 5F‐MDMB‐PICA) show a higher potency at CB1, when compared with their L‐valinamide or methyl L‐valinate analogs. Some major metabolites of SCs retain their activity ‐with a lesser extent than the parent compound.